The exponential correlation function in the mathematical model of the investigated channel differential correlator with unmanned aerial vehicles - Vladimir Pavlovich Gerasimov; Vladimir Danilovich Kovalev; Sergey Vladimirovich Gerasimov; Alexander Yurievich Darzhania (Наука. Инновации. Технологии)
Prevention, detection, localization of emergency situations in the early stages of their occurrence and distribution is relevant problem in the modern world. Russia differs from other countries in the world a vast territory and a low average population density, so the labour resources is not enough to meet these goals. Unmanned aerial vehicles may to solve this problem. The article discusses correlation-extremal systems in control for drones and analyzes the differential method of determining the extremum in the on-Board discriminators - economical from the point of view of the resource requirements of an onboard computer and performance, allowing to solve tasks in real time. The computer analysis demonstrated the presence of methodological errors that need to be considered in the design of airborne tracking systems (correlators) drones. Knowledge of the causes of methodical errors in the channels of the differential correlator makes it possible to develop measures for their compensation, using for the sensors of unmanned aerial vehicles the positive qualities of this method.